CONFORMATIONAL-CHANGES OF THE LECITHIN HEADGROUP IN MONOLAYERS AT THE AIR/WATER INTERFACE - A NEUTRON REFLECTION STUDY - Brumm, T; Naumann, C; Sackmann, E; Rennie, A; Thomas, R; Kanellas, D; Penfold, J; Bayerl, T (1994)
The headgroup conformation of the phospholipid dipalmitoyl-glycero-phosphocholine (DPPC) in monolayers at the air/water interface has been studied by neutron reflection in the fluid like liquid-expanded (LE) and in the crystal like solid (S) phase. Information on the headgroup conformation in the two phases has been obtained by scattering contrast variation of the lipid monolayer using four differently deuterated species of DPPC: perdeuterated, chain perdeuterated, choline group perdeuterated and selectively headgroup deuterated. Since the measurements were done mainly on a subphase of null reflecting water (i.e. water scattering contrast matched to the air) there is no subphase contribution to reflectivity and the simplest one layer model can be employed for the data analysis, thus minimising the number of free parameters. A remarkable change of the headgroup orientation was observed between the LE and the S phase. We found that the phosphate-nitrogen dipole of the DPPC headgroup exhibits an in-plane orientation with respect to the monolayer in the LE phase but it assumes a more parallel orientation to the surface normal at lateral pressures above 30 mN/m (S phase). Moreover, this conformational change is accompanied by a significant alteration of the headgroup hydration. © 1994 Springer-Verlag.